Effect of caffeine supplementation on anaerobic and aerobic performance in sleep-restricted male college soccer players - Cheng, Ruiqi; Wang, Ning; He, Weili; Zhou, Zeng; Chen, Zhen; Li, Xiaotian (Frontiers in Physiology, 2025)
This study aimed to explore the effects of sleep restriction of ≤5 h within 24 h on anaerobic and aerobic performance in male college soccer players and evaluated the effects of acute supplementation of 3 mg⋅kg−1 caffeine on the aerobic and anaerobic performance of college male soccer players under sleep restriction. Methods: 10 college male soccer players were recruited, and a randomized crossover experimental design was adopted. The subjects received three intervention treatments in a randomized crossover order: Normal sleep night (NSN), sleep restriction night supplemented with placebo (SRP), and sleep restriction night supplemented with 3 mg⋅kg−1 caffeine (SRC), and participated in the Running-Based Anaerobic Sprint Test (RAST) and 30-15 Intermittent Fitness Test (30-15IFT). Results: The main effect of the RAST and the 30-15IFT scores was significant (P<0.05). Post hoc analyses showed that the peak power, mean power, peak power/body mess, mean power/body mess, peak velocity mean velocity, fatigue index of the RAST, and the velocity of the intermittent fitness test (VIFT), maximal oxygen uptake (VO2max), and time to exhaustion (TTE) of the 30-15IFT in the SRP group were significantly lower than those of the NSN group (P < 0.05), and the total time of the RAST was significantly higher than that of the NSN group (P < 0.05); there were significant differences between the VIFT, VO2max and TTE indicators tested at 30-15IFT between the SRC group and the SRP group (P < 0.05). Still, other indicators had no significant differences (P > 0.05). Conclusion: Sleep restriction harms the anaerobic repeated sprint and aerobic performance of college soccer players; acute supplementation of 3 mg⋅kg−1 of caffeine can effectively reduce the negative impact of insufficient sleep the night before on the aerobic endurance performance of college soccer players. Athletes or coaches should consider caffeine supplementation as a strategy to alleviate the negative impacts of sleep deprivation, but individual tolerance and potential side effects should be taken into account.